A Little Kingdom. Local Exposures of the Interwar Lithuania (a Case Study) - Matulytė, Margarita (Tautosakos darbai, 2017)
Based on a case study, the article deals with a question of factors that affect reading of photography and the image it creates, and how different interpretative approaches can alter it. The investigation focuses on a Marcišauskai family picture taken in 1938 in Gudaičiai village (Šiauliai district) during fieldwork session organized by the Šiauliai Society of Regional Studies. Historical context included in the discussion of the photo (from intentions of the photographer to social and cultural circumstances shaping the identity) expands the limits of confiding in the image and highlights the problem of cognizability of the visual text. Purposefully chosen contextual material supplies information regarding the authentic village culture. The quest for interpretative approaches to the perception of the portrait of Lithuanian family involves discussing an associative analogue – an iconic German photograph from 1914 by August Sander, entitled “The Young Farmers”, which, aside from its key purpose clearly articulated by the photographer, can raise entirely different questions and generate new meanings. Some knowledge of the authentic surroundings and the family history of the photographed people shapes our attitude to the image that refers to just a momentary state of being, and broadens our scope of perception. True, the context does not prove the existence of the ethic categories and meanings noted in the photograph, but it deepens and enriches our view. The visible image, the contextual experience, and implicit attitudes of the heroes, the photographer’s tactics, style, aims, and the connecting link, i. e. the connotations, cultural readiness and attitude of the reader – all these affect the reading of the image. Often, photograph stands out as a reliable source of cognition, as an unquestionable documentary evidence of real events; however, the circumstances of its creation, determining adequacy of the information and reality, usually skip our attention. On the other hand, photographs also function as esthetic phenomena, liable to applying artistic, phenomenological and even psychoanalytic interpretations to the perception of their cultural meanings. An indiscriminative attitude to the visual text may result in getting lost between layers of meaning. Describing the image and giving sense to it require posing problematic questions regarding to who creates the photo texts, in what way and why; as well as to who influences the interpretations of the visual meanings and in what way.